2022
DOI: 10.1007/s10653-022-01384-9
|View full text |Cite
|
Sign up to set email alerts
|

The human health risk assessment and countermeasures study of groundwater quality

Abstract: Background:Groundwater serves as the drinking water source, which chemical components directly affect human health. Different regions own their groundwater hydro-chemical characteristics based on various geological, hydro-geological conditions, human activities. From the perspective of human health, it is necessary to select groundwater quality health risk assessment (GQHR) factors combined with 2 hydro-chemical characteristics of different regions. Methods:In this paper, taking Tongzhou of Beijing,China as th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…This paper uses a health risk assessment model recommended by the U.S. Environmental Protection Agency (USEPA) to evaluate the groundwater quality in the oil shale mining areas [28][29][30][31]. There are many ways for pollutants in water to enter the human body [32,33], and many studies have confirmed that direct consumption is the most harmful to human health [34][35][36][37].…”
Section: Health Risk Assessment Methodsmentioning
confidence: 99%
“…This paper uses a health risk assessment model recommended by the U.S. Environmental Protection Agency (USEPA) to evaluate the groundwater quality in the oil shale mining areas [28][29][30][31]. There are many ways for pollutants in water to enter the human body [32,33], and many studies have confirmed that direct consumption is the most harmful to human health [34][35][36][37].…”
Section: Health Risk Assessment Methodsmentioning
confidence: 99%
“…In addition to books, there has been a large number of journal articles published over the past two decades, with the number of journals focusing on geological factors and human health also increasing. Some examples of these journals include Exposure and Health, Human and Ecological Risk Assessment, and Environmental Geochemistry and Health, presenting many papers reporting on the effects of geoenvironmental factors on human health [26][27][28][29][30]. In addition, some water-and geology-related journals also published a number of papers regarding water quality and public health [31][32][33].…”
Section: Recent Research Advances In Groundwater Quality and Public H...mentioning
confidence: 99%
“…Compared with surface water, groundwater is less disturbed by external factors and can ensure a continuous and stable supply of good-quality fresh water over long time periods ( Aeschbach-Hertig and Gleeson, 2012 ; Griebler and Avramov, 2015 ). However, human reliance on groundwater is increasing, and human activities are gradually affecting the quality of groundwater and ecological balance ( Danielopol et al, 2003 ; Gerth and Förstner, 2004 ; Li et al, 2018 ; Ren and Zhang, 2020 ; Zhou B. et al, 2021 ; Lan et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%